Samira surfs - Guidroz, Rukhsanna (Kokila, 2022)
After her family flees violence in Burma, eleven-year-old Samira and her family have tried to make a new life for themselves in Bangladesh, working as unregistered refugees and surviving hostility from locals. While selling hard boiled eggs to beach tourists, Samira is introduced to a surfing club for females and discovers an outlet that offers her the freedom to believe in herself.